Yes-associated protein up-regulates Jagged-1 and activates the NOTCH pathway in human hepatocellular carcinoma - Tschaharganeh, Darjus-Felix; Chen, Xin; Latzko, Philipp; Malz, Mona; Gaida, Matthias; Felix, Klaus M.; Ladu, Sara; Singer, Stephan; Pinna, Federico; Gretz, Norbert; Sticht, Carsten; Tomasi, Maria Lauda; et al. (Gastroenterology, 2013)
Background & Aims - Cancer cells often lose contact inhibition to undergo anchorage-independent proliferation and become resistant to apoptosis by inactivating the Hippo signaling pathway, resulting in activation of the transcriptional co-activator yes-associated protein (YAP). However, the oncogenic mechanisms of YAP activity are unclear. - Methods - By using cross-species analysis of expression data, the Notch ligand Jagged-1 (Jag-1) was identified as a downstream target of YAP in hepatocytes and hepatocellular carcinoma (HCC) cells. We analyzed the functions of YAP in HCC cells via overexpression and RNA silencing experiments. We used transgenic mice that overexpressed a constitutively activated form of YAP (YAPS127A), and measured protein levels in HCC, colorectal and pancreatic tumor samples from patients. - Results - Human HCC cell lines and mouse hepatocytes that overexpress YAPS127A up-regulated Jag-1, leading to activation of the Notch pathway and increased proliferation. Induction of Jag-1, activation of Notch, and cell proliferation required binding of YAP to its transcriptional partner TEA domain family member 4 (TEAD4); TEAD4 binding required the Mst1/2 but not β-catenin signaling. Levels of YAP correlated with Jag-1 expression and Notch signaling in human tumor samples and correlated with shorter survival times of patients with HCC or colorectal cancer. - Conclusions - The transcriptional regulator YAP up-regulates Jag-1 to activate Notch signaling in HCC cells and mouse hepatocytes. YAP-dependent activity of Jag-1 and Notch correlate in human HCC and colorectal tumor samples with patient survival times, suggesting the use of YAP and Notch inhibitors as therapeutics for gastrointestinal cancer. Transcript profiling: microarray information was deposited at the Gene Expression Omnibus database (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?token=jxepvsumwosqkve&acc=GSE35004).
Gesehen am 14.02.2022